Characterization of tailocins of Pragia fontium 24613 and the tailocin loci within the family Budviciaceae - Snopková, Kateřina; Chaloupková, Eva; Hrala, Matěj; Šmajs, David (Research in microbiology, 2025)
Tailocins are nano-scale phage tail-like protein complexes that can mediate antagonistic interactions between closely related bacterial species. While the capacity to produce R-type tailocin was found widely across Gammaproteobacteria, the production of F-type tailocins seems comparatively rare. In this study, we examined the freshwater isolate, Pragia fontium 24613, which can produce both R- and F-type tailocins. We investigated their inhibition spectrum, focusing on clinically relevant enterobacteria, and identified the associated tailocin gene cluster. Transmission electron microscopy confirmed that inactivation of the tape measure protein within the tailocin cluster disrupted R-tailocin production. Comparative analysis of Budviciaceae gene clusters showed high conservation of R-type tailocin genes, whereas F-type tailocin genes were found in only a few species, with little conservation. Our findings indicate a high prevalence of bacteriocin production among underexplored Enterobacteriales species. Detected tailocins showed potential as antimicrobials targeting clinically significant pathogens.
Keywords: Enterobacteriaceae; Multigene Family; Antibiotics; Phylogeny; antibakteriální látky; Enterobacteria; Bacteriocins; bakteriociny; multigenová rodina; Anti-Bacterial Agents; Yersinia enterocolitica; Phage tail-like particle; Bacteriophages; Fonticin; fylogeneze; Antimicrobial agent; bakteriofágy